Ciencia e investigación agraria 2018
DOI: 10.7764/rcia.v45i2.1887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental variables on PCDD/F and dl-PCB levels in dairy milk of the farming region of Chile

Abstract: Impact of environmental variables on PCDD/F and dl-PCB levels in dairy milk of the farming region of Chile. 2018. Cien. Inv. Agr. 45(2): 109-119. According to a One Health perspective, the importance of persistent organic pollutants (POPs) must be assessed because of their impact on the environment, food chain and human health. However, information on these toxic compounds is limited in Latin America and the Caribbean region. Chile is no exception; therefore, this work aimed to explain previously reported diox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The PCBs are persistent and could be accumulated in livestock products, differently to PAHs that are largely metabolised [ 2 , 78 ]. In animal products, these contaminants can achieve different pollution levels, and dairy products represent a considerable portion of total dietary exposure, considering the human diet composition [ 3 ]. The cheeses sampled in this study showed a presence of dl- PCBs 114 + 118 (range: 0.01–5.41 ng/g; Table S2 ), being that PCB 118 is one of the principal congeners found in cow milk [ 92 , 93 , 94 ], a raw product used to make Caciocavallo Palermitano cheese.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PCBs are persistent and could be accumulated in livestock products, differently to PAHs that are largely metabolised [ 2 , 78 ]. In animal products, these contaminants can achieve different pollution levels, and dairy products represent a considerable portion of total dietary exposure, considering the human diet composition [ 3 ]. The cheeses sampled in this study showed a presence of dl- PCBs 114 + 118 (range: 0.01–5.41 ng/g; Table S2 ), being that PCB 118 is one of the principal congeners found in cow milk [ 92 , 93 , 94 ], a raw product used to make Caciocavallo Palermitano cheese.…”
Section: Resultsmentioning
confidence: 99%
“…Many works show the risks involved due to the occurrence of persistent organic pollutants (POPs) in the environment, affecting negatively both ecosystems and human health [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Only a few investigations were carried out on transfer of POPs to cow milk and the subsequent human risk by ingestion of dairy products [ 1 , 2 , 4 , 6 , 8 , 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations